Use of Personal Protective Equipment (Gloves) Can Reduce the Risk of Damage to Skin Integrity in Fish Packaging Workers - Zaini S; Clariesta W; Handoko I; Widiastuti A (LPPM Universitas Duta Bangsa Surakarta, 2021)
One of the health problems for fish packaging workers due to work is damage to the integrity of the skin. Some of the factors that can cause damage to skin integrity are age, years of service, history of skin diseases, personal hygiene, and use of personal protective equipment. Damage to skin integrity is inflammation of the skin caused by a substance in contact with the skin. The purpose of this study was to determine the effect of using personal protective equipment (gloves) on the risk of damage to skin integrity. The method used is quantitative research using a descriptive correlation approach. Cross Sectional. Sampling using total sampling technique, with a total sample of 52 respondents, while the research instruments using a questionnaire and checklist. Bivariate analysis using the Chi Square test. The results obtained from the bivariate test proved that the use of personal protective equipment (gloves) had an effect on the risk of damage to skin integrity. The conclusion is that there is an effect of using personal protective equipment (gloves) on the risk of damage to skin integrity in fish packaging workers.